CORRELATION BETWEEN FASTING BLOOD SUGAR AND LDL CHOLESTEROL OF TYPE 2 DM PATIENTS ON WILLIAM BOOTH HOSPITAL SEMARANG - Ragil Saptaningtyas; Regitha Wahyuhendra; Joko Teguh Isworo (Universitas Negeri Gorontalo, 2022)
Type 2 diabetes mellitus is a metabolic disorder characterized by hyperglycemia as a result of reducing insulin secretion of pancreas beta cells or insulin function disorder. Type 2 DM can cause lipid metabolism disorder (dyslipidemia) such as increasing total cholesterol, triglyceride, and decreasing HDL levels. The small and dense , Rafparticle of LDL is susceptible to oxidation, so it makes LDL more atherogenic than other lipoproteins. A high level of LDL is a factor in atherosclerosis. It can be affected by patients' lifestyles. The aim of this study is to figure out the relation between fasting blood sugar and LDL Cholesterol of Type 2 DM Patients on William Booth Hospital Semarang. This study used secondary data taken from 85 patients from the medical report and laboratory test results of William Booth Hospital Semarang from January to May 2021 that fit inclusion and exclusion criteria. Result data were analyzed by a statistical test with Spearman's correlation test. The result of this study showed that 96,5% of patients had high levels of fasting blood sugar and 76,4% of high levels of LDL cholesterol, with Spearman's correlation p-value was 0,977. The study concluded that there is no meaningful correlation between fasting blood sugar and LDL cholesterol of type 2 DM patients on William Booth Hospital Semarang.